2012
DOI: 10.3109/0142159x.2012.658897
|View full text |Cite
|
Sign up to set email alerts
|

Improving the accuracy of self-assessment of practical clinical skills using video feedback – The importance of including benchmarks

Abstract: The demonstration of a video-recorded benchmark performance in combination with video feedback may significantly improve the accuracy of students' self-assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 24 publications
2
55
0
2
Order By: Relevance
“…[18][19][20][21] When peer ratings are included in the mix, peer ratings rank in favorability between faculty member and self-ratings. 14,17,[22][23][24][25][26][27] It has frequently been found that the overassessment bias is stronger for students who perform poorly than for those who perform well. 6,[28][29][30][31][32][33][34][35] Such an effect requires an explanation beyond saying that it is a deicient understanding of the criteria on students' parts.…”
Section: Building a Model Of The Effect Of Self-assessment On Learningmentioning
confidence: 99%
“…[18][19][20][21] When peer ratings are included in the mix, peer ratings rank in favorability between faculty member and self-ratings. 14,17,[22][23][24][25][26][27] It has frequently been found that the overassessment bias is stronger for students who perform poorly than for those who perform well. 6,[28][29][30][31][32][33][34][35] Such an effect requires an explanation beyond saying that it is a deicient understanding of the criteria on students' parts.…”
Section: Building a Model Of The Effect Of Self-assessment On Learningmentioning
confidence: 99%
“…A culture of challenging school examination outcomes may also play a part: in 2016, Ofqual, the UK body overseeing school assessments taken at age 16 years, reported that 18% of all General Certificate of Education/General Certificate of Secondary Education grades were challenged . In addition, there is evidence that candidates may genuinely overestimate their own performance and are not able to benchmark themselves without assistance . So it is perhaps unsurprising that learners question assessment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It was postulated that video feedback would be sufficient to improve self-assessment [63]. A study by Hawkins and colleagues achieved improvement only retrospectively when a video of the students’ performance was juxtaposed a video demonstrating the correct manoeuvres [64]. It is therefore important to give the students a good idea of their performance through structured feedback, but also to show the correct execution of the skill assessed.…”
Section: Discussionmentioning
confidence: 99%